Discovery of novel targets in a complex regional pain syndrome mouse model by transcriptomics: TNF and JAK-STAT pathways. (August 2022) - Pohóczky, Krisztina; Kun, József; Szentes, Nikolett; Aczél, Tímea; Urbán, Péter; Gyenesei, Attila; Bölcskei, Kata; Szőke, Éva; Sensi, Serena; Dénes, Ádám; Goebel, Andreas; Tékus, Valéria; et al.
Abstract: Complex Regional Pain Syndrome (CRPS) represents severe chronic pain, hypersensitivity, and inflammation induced by sensory-immune-vascular interactions after a small injury. Since the therapy is unsatisfactory, there is a great need to identify novel drug targets. Unbiased transcriptomic analysis of the dorsal root ganglia (DRG) was performed in a passive transfer-trauma mouse model, and the predicted pathways were confirmed by pharmacological interventions. In the unilateral L3–5 DRGs 125 genes were differentially expressed in response to plantar incision and injecting IgG of CRPS patients. These are related to inflammatory and immune responses, cytokines, chemokines and neuropeptides. Pathway analysis revealed the involvement of Tumor Necrosis Factor (TNF) and Janus kinase (JAK-STAT) signaling. The relevance of these pathways was proven by abolished CRPS IgG-induced hyperalgesia and reduced microglia and astrocyte markers in pain-associated central nervous system regions after treatment with the soluble TNF alpha receptor etanercept or JAK inhibitor tofacitinib. These results provide the first evidence for CRPS-related neuroinflammation and abnormal cytokine signaling at the level of the primary sensory neurons in a translational mouse model and suggest that etanercept and tofacitinib might have drug repositioning potentials for CRPS-related pain. Graphical Abstract: ga1